“ETAIKEN WEREK”: HATI MENURUT ORANG HUWULA - Meki Mulait (Studi Budaya Nusantara, 2017)
AbstractThe role of the heart is very important in human life. The heart is not only synonymous with feeling but also has a rational intuitive. With careful human life develops in a balanced and meaningful. Thereby heart being one of the central human strength that should be put forward. Forward the heart does not mean ignoring other powers such as seeing, feeling, thinking, and acting up to the soul and spirit in relation to the Supreme Being. Putting forward the 'heart' means